PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP MINAT BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS DI SDN 182 PEKANBARU - Wulan Dari; Elpri Darta Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning interest of fourth-grade students in the Natural and Social Sciences (IPAS) subject, which was caused by a learning process that did not actively engage students. The purpose of this study was to determine the effect of the Problem Based Learning (PBL) model on the learning interest of fourth-grade students in the IPAS subject at SDN 182 Pekanbaru. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of all fourth-grade students at SDN 182 Pekanbaru, while the sample included an experimental class and a control class selected through purposive sampling. The research instrument was a learning interest questionnaire that had been tested for validity and reliability. Data were analyzed using normality and homogeneity tests, followed by hypothesis testing through the Independent Samples t-test. The findings revealed that the implementation of the Problem Based Learning (PBL) model had a significant effect on students' learning interest in the IPAS subject. Students who participated in learning through the Problem Based Learning (PBL) model demonstrated higher learning interest than those who received conventional instruction. Therefore, the Problem Based Learning (PBL) model can be considered an effective alternative instructional model to enhance students' learning interest in IPAS learning at the elementary school level.